Jazan University faculty members’ trends toward using the "Blackboard Platform" electronic learning tools in the scientific process in line with the consequences of Coronavirus - Alsaeed, Batool AbdElbagi Abdalla (Journal of Educational and Psychological Sciences, 2020)
The study aims at identifying the trends of Jazan University faculty toward employing e-learning tools the Blackboard platform in the educational process, the descriptive approach was used, as the tool was to represent in a resolution distributed to a sample of (90) members of Jazan University faculty teaching staff, and the researcher reached several results: * the faculty staff employ plaque board tools in simultaneous e-learning and have received an average (4.15 out of 5) (large) grade of scientific and conceptual college student preparation with an average arithmetic (3.88). And (large) while faculty trends toward the application of the plaque board platform were safe and effective in evaluation Student work with an average (2.99) and a (medium) score, while sharing forums, in interactive activities, open-ended tests, was average (2.20) to a small (few) degree. The results also showed that there were no statistically significant differences among the sample population in the trends toward the application of the plaque board tools in the process Teaching staff members according to variables (type/specialization/grade), the researcher made a series of recommendations and proposals; the most important of which are: The need to apply specialized training programs in educational institutions to faculty and students, and to conduct research on the effectiveness of using assessment tools through the Blackboard platform, supporting education E-learning by departments and educational institutions, use the active learning strategies available through the Blackboard platform and the variety of the provision of learning material to the learner, which will lead to its full benefit and increased educational attainment. Intensifying efforts and follow-up by the leadership of e-education and information technology Universities to make full use of.